13th International Conference on Kinanthropology. Sport and Quality of Life Book of Abstracts. September 7-9, 2022 - Cacek, Jan (Masaryk University Press, 2022)
The book of abstracts of the 13th Conference of Sport and Quality of Life 2022 gathers the abstracts of all the oral and poster presenters and keynote speakers. The conference is divided into sections - analysis of human movement; sport training; healthy lifestyle, active aging, nutrition and regeneration in sport; sport and social sciences; sports medicine; and the poster section.